Pengaruh Kegiatan Akademik Terhadap Penguatan Karakter Civic Responsibility Mahasiswa Ppkn Fkip Universitas Lampung - Anisatul Mustafidah; Berchah Pitoewas; Nurhayati Nurhayati; Muhammad Mona Adha; Rohman . (Jurnal Pendidikan Sosial Dan Konseling, 2026)
This study aims to determine the effect of academic activities on strengthening the civic responsibility character of students in the Civics and Citizenship Education Study Program, Faculty of Teacher Training and Education, University of Lampung. The research method used was quantitative with a descriptive approach. The sample size was 76 students from the 2022–2024 intake. Data collection techniques used questionnaires, tests, and interviews. Data analysis used simple linear regression with SPSS 25. The results showed a significant effect of academic activities on strengthening civic responsibility character, with a significance value of 0.000 (p < 0.05) and a coefficient of determination of 0.991. This indicates that academic activities contribute 99.1% to strengthening civic responsibility character. Academic activities such as scientific discussions, seminars, and involvement in research and community service have been shown to increase students' social participation, awareness, and responsibility as citizens.